1980
DOI: 10.1021/ja00530a040
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur as a regiochemical control element. Synthesis of 2-alkoxy(acyloxy)-3-alkyl(aryl)thiobuta-1,3-dienes

Abstract: The internal competition between substituents in the 2,3 positions of a diene-one being a sulfur and the other an oxygen substituent-is discussed. To examine this question, a general approach to 2-alkoxy(acyloxy)-3-alkyl(aryl)thiobuta-I ,3-dienes has been developed. Bromocyclobutanone undergoes displacement with sulfur nucleophiles without competing rearrangements of the benzylic acid type. These compounds have been 0-alkylated and 0-acylated to give 1 -alkoxy(acyloxy)-2alkyl(ary1)thiocyclobutenes. Thermal ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Silylation with BSA is then worth investigating. 39 It has also been shown that the charcoal carrier for tungstic acid-tributyltin chloride which is used in the catalysed hydrogen peroxide epoxidation of alkenes is improved by treatment with BSA. The decomposition of the hydrogen peroxide that is catalysed by surface hydroxyl groups is then less troublesome.…”
Section: Methodsmentioning
confidence: 99%
“…Silylation with BSA is then worth investigating. 39 It has also been shown that the charcoal carrier for tungstic acid-tributyltin chloride which is used in the catalysed hydrogen peroxide epoxidation of alkenes is improved by treatment with BSA. The decomposition of the hydrogen peroxide that is catalysed by surface hydroxyl groups is then less troublesome.…”
Section: Methodsmentioning
confidence: 99%
“…13, the sulfur analog 17 produces the meta type of product 18 (Eq. 15) (19,20). While desulfurization methodology permits replacement of a C-S bond with a C-H bond, the sulfur substituent provides synthetic versatility, as demonstrated by its elimination to 19.…”
Section: Regioselectivitymentioning
confidence: 99%
“…85 2-Alkoxy(acyloxy)-3-alkyl(aryl)thiocyclobutadienes are converted into the corresponding dienes on heating to 350 8C as the result of the cleavage of the C(1) ± C(4) bond in the rings. 86 Pyrolysis of 3,4-bis(methylthio)cyclobutene-1,2-dione at 450 8C leads to the ring opening with the formation of bis(methylthio)acetylene and CO. At 550 8C, hydrogen sulfide and methanethiol are also formed in this reaction. 87 Allyl and propargyl 1,1-dicyano-2-ethoxyvinyl sulfides undergo the Claisen rearrangement on distillation being converted into the corresponding O-ethyl thiocarboxylates 29.…”
Section: Vinyl and Ethynyl Sulfidesmentioning
confidence: 99%